Optimization of the Quality of Chestnut Rose Jiaosu Compound Beverage Based on Probiotic Strains and Fermentation Technology - Shiping Zou; Yao Xu; Biao Huang (Journal of Food Quality)
Chestnut rose is an endemic plant in Guizhou Province, China, also known as seedless prickly pear, rich in mineral elements, vitamin C, and flavonoids. With chestnut rose as the main raw material, with grapes, apples, and other fruits as auxiliary ingredients, through the technical process of deastringency, sterilization, fermentation, blending, and other technical processes to obtain the composite beverage, known as a chestnut rose jiaosu compound beverage, it is hereinafter referred to as CRJCB. The CRJCB fermented from chestnut rose juice is nutritious and has a variety of health effects, and the flavor is unique, with good color, aroma, and taste, which is a new type of beverage. However, at present, the fermentation related technology of CRJCB is not perfect, resulting in its low quality, which seriously restricts the industrialization development of CRJCB. In order to improve the quality of the jiaosu compound beverage, probiotics such as Lactobacillus delbrueckii subsp. Bulgaricus, Lactobacillus casei, Lactobacillus royale (Lactobacillus reuteri), Lactobacillus acidophilus, and Streptococcus thermophilus, etc., were used. The chestnut rose as the main raw material was used for the fermentation, and grapes, apples, and sugar were used as auxiliary materials to carry out the research on the fermentation of single or mixed probiotics. The key fermentation processes affecting the quality of the jiaosu, such as juice preparation, deastringency of chestnut rose juice, fermentation temperature and time, sugar addition, and taste mixing of the jiaosu, were optimized. The optimized ratio, fermentation process parameters, and strains of probiotics of compound beverage with chestnut rose jiaosu, with high quality, were obtained. The experimental results showed that the SOD enzyme activity value was 167.7 U·ml−1, the vitamin C content was 1154.5 mg/100 mL, the soluble solids content was 5.80%, and the nitrite content was 89.8 mg/kg in the compound beverage with chestnut rose jiaosu, obtained by using the optimized ratio and fermentation process parameters proposed in this paper. The development and utilization of chestnut rose resources provide a new idea and is of great significance in promoting the development of the chestnut rose industry.